Analisis Peran Manajemen Risiko pada Produk Gadai Emas di Pegadaian Syariah Ngabul Jepara - Shofi’atun Ni’mah; Wahidullah; Zahrotun Nafisah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Sharia Pawnshop is a financial institution that provides pawn services based on sharia principles, including gold pawning products that carry specific risks. This study aims to analyze the risk management applied to gold pawning products at the Sharia Pawnshop in Ngabul Jepara. The research method used is a qualitative approach with a descriptive analysis. Data were collected through in-depth interviews with Sharia Pawnshop officials, direct observations, and literature studies from various relevant sources. The study results indicate three main types of risks in gold pawning products: market risk, credit risk, and operational risk. Market risk is related to gold price fluctuations that may affect the collateral value. Credit risk arises from potential customer defaults, while operational risk stems from errors in transaction processes and gold appraisal. The Ngabul Jepara Sharia Pawnshop has implemented risk mitigation strategies, such as strict customer evaluations, adjusting collateral value based on current gold prices, and strengthening internal supervision. The study concludes that effective risk management is essential to maintaining the stability and sustainability of Sharia Pawnshop operations. The findings of this study can serve as a reference for developing more optimal risk mitigation strategies in Islamic financial institutions.